2015
DOI: 10.1007/s11205-015-1100-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Affecting Health Indicators in Sub-Saharan African Countries: Health is Wealth

Abstract: Sub-Saharan African countries faced severe environmental hazards that affect the health and wealth of the countries. The study utilized number of environmental factors including carbon dioxide emissions, energy use, fossil fuel energy consumption, land used under cereal production, household final consumption expenditures and water sanitation facility that have a promising impact on African's health. The study considered four health variables including external resources for health, health expenditures per cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…The policy should be devised to conserve natural environment by using sustainable instruments that would limit the macroeconomic factors for healthy and wealthy life. Zaman et al (2015a) examined the health and wealth relationship in Sub-Saharan African countries and confirm the strong correlation between them. Ozturk (2015a) emphasized the need to control domestic and global air pollutants for mitigating the climatic concern across the countries.…”
Section: Literature Reviewmentioning
confidence: 83%
“…The policy should be devised to conserve natural environment by using sustainable instruments that would limit the macroeconomic factors for healthy and wealthy life. Zaman et al (2015a) examined the health and wealth relationship in Sub-Saharan African countries and confirm the strong correlation between them. Ozturk (2015a) emphasized the need to control domestic and global air pollutants for mitigating the climatic concern across the countries.…”
Section: Literature Reviewmentioning
confidence: 83%
“…By analyzing Sub-Saharan African Countries, Zaman et al [45] found out that although increasing consumption of fossil fuel energy is associated with GDP growth, and implicitly the possibility of additional health allocations and increased life expectancy, it is also associated with carbon dioxide emissions, which increase spending on health per capita. On one hand, increases in life expectancy significantly decrease the health care provisions of per capita health levels; on the other hand, life expectancy is negatively affected by poor sanitation and low environmental protection spending levels, which also adds to the budgets dedicated to healthcare expenditures.…”
Section: Health Expenditure Economic Growth and Air Pollutionmentioning
confidence: 99%
“…Numerous number of researchers [1][2][3], have examined the impact of economic growth, energy use and population on carbon emissions in Sub-Saharan Africa. The relationship between economic growth, energy use, population and environmental pollution has been a topic of concern for several years [27,28]. Different methods and strategies have been applied by researchers to examine the relationship between economic growth and energy use and secondly, to investigate the relationship between economic growth and carbon emissions to validate the legitimacy of the EKC hypothesis.…”
Section: Methodsmentioning
confidence: 99%